Role of subcutaneous treatment in home based palliative care - Lobo, Filipa Almada (2007)
Introduction: From 60 to 70% of palliative care patients become unable, during the disease course, to take drugs using the oral route (OR). Since palliative care should ideally be home-based, the most simple and suitable application method should be provided. The subcutaneous route (SR) is easier than the endovenous route to use at home: theres no need of health professionals, it is less painful and can be used for longer periods. Case Description: 45-year-old woman, public servant until March 2005; Graffar level IV and Family APGAR score of 9; lived with her husband until that date, and since then also with her mother. No children. No relevant personal history; she had a family history of pancreas cancer in her dead father. In March 2005, she visited her family doctor for weight loss, asthenia, abdominal pain and vomiting. After the investigation, she had been diagnosed sigmoid colon cancer with hepatic metastases. In May, she was referred to Portuguese Oncology Institute (POI) of Porto, where she was performed a colectomy and colostomy. Between June and October, due to uncontrolled pain and/or vomiting, she seeked the emergency service (ES), despite her physical disabilities. In October, she went to the continuous care unit of POI. By her choice, she is currently at home with a health assistant. Whenever OR can not be applied due to frequent vomiting, SC was choosen to achieve control of symptoms. Discussion: Based on this case report, the author highlights situations of palliative care in which patients can stay at home with controlled symptoms, using SR, and shows that an earlier home-based health assistant could have avoided the frequent patient visits to ES. Since one of the family doctors functions is to deliver home health care to terminal patients, he or she must be familiar with this drug administration route.